The short, the long and the tall : short stories - Archer, Jeffrey, 1940- (St. Martin's Press, 2020)
"New York Times number one bestselling author Jeffrey Archer is a master of the short-story form, creating classic tales beloved by his fans. Now the award-winning writer joins forces with renowned illustrator Paul Cox to re-imagine twenty of his most popular and fêted short stories alongside beautifully rendered watercolor illustrations in The Short, The Long and the Tall. Find out what happens to the hapless young detective from Naples who travels to an Italian hillside town to solve a murder and ends up falling in love; and the pretentious schoolboy whose discovery of the origins of his father's wealth changes his life forever. Revel in the stories of the woman who dares to challenge the men at her Ivy League university during the 1930s, and another young woman who thumbs a lift and has an encounter she will never forget. Discover the haunting story about four men whose characters are tested to the point of death. Finally, a short parable about how pointless war is, and how decent people are caught up in the crossfire of their leaders' ambitions. This will be a must-buy for dedicated fans of the work of both author and illustrator, and includes the following short stories: Never Stop on the Motorway Cheap At Half the Price Who Killed the Mayor? It Can't Be October Already Stuck on You The Grass is Always Greener The Queen's Birthday Telegram Clean Sweep Ignatius The First Miracle Caste Off A Wasted Hour Just Good Friends Christina Rosenthal A Gentleman and a Scholar The Road To Damascus Old Love A Good Toss To Lose One Man's Meat Endgame Confession"--